2020
DOI: 10.1016/j.tecto.2020.228350
|View full text |Cite
|
Sign up to set email alerts
|

Precambrian deformation belts in compressive tectonic regimes: A numerical perspective

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 86 publications
3
13
0
Order By: Relevance
“…(A6) is satisfied (e.g. Popov and Sobolev, 2008). The viscosity for the dislocation and Peierls creep flow law is a function of the second invariant of the respective strain rate componentsε Figure A1.…”
Section: Discussionmentioning
confidence: 98%
“…(A6) is satisfied (e.g. Popov and Sobolev, 2008). The viscosity for the dislocation and Peierls creep flow law is a function of the second invariant of the respective strain rate componentsε Figure A1.…”
Section: Discussionmentioning
confidence: 98%
“…Numerical models suggest that transitional tectonics occurred at mantle temperature up to 200 • C higher than today and was triggered by the generation of continental crust and the stabilisation of cratons (e.g., Sizova et al, 2010Sizova et al, , 2015Perchuk et al, 2018). However, a recent thermo-mechanical study indicated that the shortening rate, which can vary over several orders of magnitude, also plays an important role (Poh et al, 2020). High shortening rates ( > 1 × 10 -15 s -𝜀 𝐵𝐺 1 ) favours the formation of asymmetric deformation zones (i.e., modern-style tectonics) while low shortening rates ( < 1 × 10 -15 s -1 ) favour the development of 𝜀 𝐵𝐺 distributed deformation zones and vertical structures (i.e., ancient-style tectonics).…”
Section: Strength Of the Lithosphere And Parameters To Testmentioning
confidence: 99%
“…The regional strain field (Fig. 5d), characterized by steeply dipping anastomosing fault systems that extend over several hundred kilometres along strike, is interpreted as resulting from the horizontal shortening and vertical stretching of a weak lithosphere during Paleoproterozoic orogens (Gapais, 2018;Poh et al, 2020;Ledru et al, 2022). In this model, deeply rooted structures like the Wollaston-Mudjatik Transition Zone, the Snowbird Tectonic Zone/Virgin River shear zone and the Patterson Lake corridor, are responsible of crustal segmentation and are natural links between deep and shallow processes.…”
Section: Sedimentary Basin-related Hydrothermal Mineralization Systemsmentioning
confidence: 99%